2016
DOI: 10.1186/s12870-016-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and evolutionary analysis of leucine-rich repeat receptor-like protein kinase genes in soybean

Abstract: BackgroundLeucine-rich repeat receptor-like kinases (LRR-RLKs) constitute the largest subfamily of receptor-like kinases in plant. A number of reports have demonstrated that plant LRR-RLKs play important roles in growth, development, differentiation, and stress responses. However, no comprehensive analysis of this gene family has been carried out in legume species.ResultsBased on the principles of sequence similarity and domain conservation, a total of 467 LRR-RLK genes were identified in soybean genome. The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 84 publications
11
88
0
Order By: Relevance
“…In this study, we have demonstrated that 16 soybean paralogous pairs derived from the second WGD, which suggests that the WGD duplication might be the main mechanism of JmjC gene family expansion and functional diversity during the evolution of soybean. This result is consistent with some other gene families not only AAT gene family (Cheng et al, 2016), GST supergene family (Liu et al, 2015), and receptor-like kinase genes (Zhou et al, 2016) in soybean, but also SET domain family in Populus trichocar (Lei et al, 2012; Zhang and Ma, 2012), and 14-3-3 family genes and AP2/ERF superfamily in M. truncatula (Qin et al, 2016; Shu et al, 2016). And in Arabidopsis , previous studies have proposed that more than 90% regulatory genes increased due to WGD (Maere et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we have demonstrated that 16 soybean paralogous pairs derived from the second WGD, which suggests that the WGD duplication might be the main mechanism of JmjC gene family expansion and functional diversity during the evolution of soybean. This result is consistent with some other gene families not only AAT gene family (Cheng et al, 2016), GST supergene family (Liu et al, 2015), and receptor-like kinase genes (Zhou et al, 2016) in soybean, but also SET domain family in Populus trichocar (Lei et al, 2012; Zhang and Ma, 2012), and 14-3-3 family genes and AP2/ERF superfamily in M. truncatula (Qin et al, 2016; Shu et al, 2016). And in Arabidopsis , previous studies have proposed that more than 90% regulatory genes increased due to WGD (Maere et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Several standard methods are reported for the characterization and comparison of different features of various genes in a gene family (Singh et al, 2015; Shumayla et al, 2016a,b; Zhou et al, 2016). The TaCaCA superfamily genes and proteins were analyzed in terms of various characteristic features like exon/intron organization, intron phase, length, molecular weight, pI, transmembrane, cytoplasmic loop size, cellular localization and domain architecture (Figure 3; Table 1; Files S4–S8).…”
Section: Resultsmentioning
confidence: 99%
“…Then, MapInspect software (http://mapinspect.software.informer.com/) was used to produce the schematic diagrams of physical locations of LRR-RLK genes in scaffolds. As previous literature, tandem duplication cluster in this study was defined as a region containing two or more genes within 200 kb (Zan et al, 2013; Zhou et al, 2016). Furthermore, tandem duplication genes should show close relationship in phylogenetic tree.…”
Section: Methodsmentioning
confidence: 99%
“…In eudicots, such as A. thaliana, Brassica rapa, Solanum lycopersicum and Populus trichocarpa , 213, 303, 234, and 379 LRR-RLK genes, respectively, have been identified from the analysis of genome sequences (Shiu and Bleecker, 2001; Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015). Based on the sequence similarity and domain conservation, as many as 467 genes were identified in the Glycine max genome (Zhou et al, 2016). In monocot Oryza sativa , 309 LRR-RLK genes were found via genome-wide identification (Sun and Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation